Secured network information resource as synergetic system - Блінцов, Володимир Степанович; Самойленко, Денис Миколайович (Ukrainian Information Security Research Journal, 2014)
The increasing complexity of modern network infomation resources, the introduction of intelligent program solutions with non-linear relationships between elements requires the use adequate mathematical tools to describe them. Existing approaches are mainly based on the means of systems analysis, cybernetics, game theory - deteminitic mathematical methods. This limits the ability to describe systems with a large number of elements and essentially with non-linear relationships between them, especially in non-equilibrium states, caused by attacks attempting on information resources. A structural model of protected information resources with the architecture conforming to the requirements of normative documentation of Ukraine and standards were proposed. The model shows the main features that are typical for a synergetic system. Application of synergetic mathematical methods will allow describing more qualitatively the processes of system deviation from equilibrium state, detecting features of the system approaches the bifurcation point, and developing tools for system diversion from nonequilibrium states.